PENGARUH MANFAAT, KEMUDAHAN, SERTA KELEMAHAN PENGGUNAAN E-MONEY DALAM MENINGKATKAN MINAT BELI KALANGAN MILENIAL DI DENPASAR, BALI - Gebriel Jivandrina Marhoin Dumais; Luh Komang Candra Dewi; Ni Luh Komang Julyanti Paramita Sari (Journal Research of Management, 2026)
This study investigates the influence of Perceived Benefits, Ease of Use, and Perceived Weaknesses of e-money on Purchase Intention among millennials in Denpasar, Bali. In the digital era, e-money adoption continues to rise, especially among younger generations who value speed and convenience in transactions. The research applied a survey method using questionnaires distributed to 100 respondents aged 20–44 years, and multiple linear regression was employed for data analysis. Results revealed that Perceived Benefits and Ease of Use significantly and positively affect Purchase Intention, while Perceived Weaknesses negatively influence it. These findings highlight that although e-money offers efficiency and practicality, concerns about security and internet dependency still hinder adoption for some users. This study provides useful insights for e-money providers to enhance service reliability, minimize weaknesses, and encourage wider acceptance among millennials.